COVID-19 in Cambodia: Impacts on Production, Poverty & Food Systems - Pradesha, Angga; Oum, Sothea; Diao, Xinshen (2021)
Prepared by Angga Pradesha1, Sothea Oum2 & Xinshen Diao1 1. International Food Policy Research Institute 2. Centre for Strategy and Innovation Policy (CSIP)